2009
DOI: 10.1249/mss.0b013e318186d843
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sports Club Participation with Fitness and Fatness in Children

Abstract: SCP rates were high and were associated with higher levels of most fitness components in children. Participation rates were lower for children of migrant families and children from inactive parents. In addition, the association between SCP and fitness components was not found in overweight children and in children from overweight parents and migrant families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 31 publications
10
59
0
6
Order By: Relevance
“…Our findings confirm cross-sectional and longitudinal data demonstrating higher aerobic fitness [16,17,38] and lower body fat [16,38] in schoolchildren participating in SC. However, a previous study found no differences in body fat [17] and hypothesized that it might be due to less actual time spent in organized sports (in most instances only once a week) [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings confirm cross-sectional and longitudinal data demonstrating higher aerobic fitness [16,17,38] and lower body fat [16,38] in schoolchildren participating in SC. However, a previous study found no differences in body fat [17] and hypothesized that it might be due to less actual time spent in organized sports (in most instances only once a week) [17].…”
Section: Discussionsupporting
confidence: 90%
“…Parental migrant status was determined according to the place of birth. Migrants were defined as at least one parent born outside Switzerland [17,32] and low educational level as at least one parent with no education beyond obligatory school (9 years). Further questions included media use (defined by time spent by children with TV viewing and video game playing (min/day)) as well as children’s and parents’ participation in a SC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Domníváme se, že takovýto široký rozsah mezi individuálními výsledky je přítomen z důvodu rozlišné míry zapojení děti do mimoškolních pohybových aktivit. Vzhledem k tomu, že PA pozitivně souvisí s úrovni TZ (Castelli, & Valley, 2007;Dencker, Thorsson, Karlsson, Lindén, Svensson, & Wollmer, 2006), dalo by se předpokládat, že zapojení do mimoškolních pohybových aktivit (aktivní transport, kroužky, sportovní trénink, účast na táborech) pozitivně ovlivňuje úroveň TZ, především kardiorespirační zdatnost (Telford, Telford, Cochrane, Cunningham, Olive, & Davey, 2016;Zahner, Muehlbauer, Schmid, Meyer, Puder, & Kriemler, 2009).…”
Section: Diskuseunclassified
“…La participación en deportes de niños y jóvenes, en su mayor parte deportes organizados, es una faceta de la AF infanto-juvenil de alto interés en el ámbito de la salud pública por su contribución al logro de una dosis adecuada de AFMV para la protección y mejora de la salud (35)(36)(37)(38)(39).…”
Section: Actividad Físicaunclassified